An active 300 GHz Down-Conversion Mixer in BiCMOS SiGe Process - Fatima, Maryam; Bolivar, Peter Haring; Choubey, Bhaskar (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
A double-balanced active Gilbert cell mixer struc-ture in Silicon-Germanium (SiGe) 130 nm technology is pre-sented. The purpose of the mixer is to down-convert the input 300 GHz radio frequency (RF) to an intermediate frequency (IF) of 50 GHz, with a local oscillator (LO) frequency of 250 GHz. Achieving conversion gain with good linearity is the main objective of this work. At 50 GHz, the designed mixer consumes 0.831 mW of power, produces a conversion gain of 3 dB, and notes a third-order intercept (IIP3) of -5.530 dBm. Implementing inductors at the output stage of the mixer makes it possible to achieve a conversion gain. Also, the conventional Gilbert cell mixer's tail current contributes to improving the mixer's linearity and is used to bias the transistors.